A retrospective study on internal fixation of femoral neck fractures with Hansson Pins® in Switzerland. Issue 6 (6th November 2022) - Conti, Tiziano; Majewski, Martin
Abstract : Background: Hansson Pins® (The Swemac Group, Linköping, Sweden) are devices for the internal fixation of femoral neck fractures that are widely used in Scandinavia. The authors hypothesized that the pins could be used with satisfactory results outside of Scandinavia, that they were a valid alternative to cancellous screws and the dynamic hip screw, and that they also could be used in elderly patients. Methods: Sixty-five consecutive patients with femoral neck fractures who received internal fixation with Hansson Pins between January 2007 and December 2016 at the Oberengadin Hospital in Switzerland were included in this retrospective study. The hospital's electronic database was searched for information, and questionnaires were sent to the patients. Results: After internal fixation with Hansson Pins, 22% of the patients needed a hip prosthesis. For patients 70 yr and older, this rate was 33%. For 60% of the patients who needed a hip prosthesis, the reason for arthroplasty was nonunion. For 20%, the reason was avascular necrosis of the femoral head, and for another 20% of the patients symptomatic coxarthrosis was the cause. Conclusions: The rate of salvage arthroplasties in this study was similar to the rates in the literature of Hansson Pins (mostly from studies performed in Scandinavia), cancellous screws and dynamic hip screws. The findings suggested that Hansson pins could be used with good results outside of Scandinavia and that they were a reasonable alternative to cancellous screws and the dynamic hip screw. The pins also could be used with satisfactory outcomes in elderly patients, but the rate of salvage arthroplasties would be higher. Level of Evidence: Level IV.